Estudos em meio poroso heterogêneo sujeito a bombeamentos periódicos - Ferreira, Lucival Amélio de Barros (1969)
The purpose of this work is the behavioral study of a heterogeneous porous media, when it suffers an unsteady periodic pumping. For this, we built a special equipment and moulded an artificial porous media to which was applied a steady contour condition upstream and the unsteady pumping was made downstream. The level variation, determined by the pulsation, beeing choosen as dependent variable, it was noticed that it proceeded like a linear function of the discharge and the period. From this function, we can make a distinction, for the case, whether the most permeable media is directly subjected to the pumping or not.